Maize hydroxycinnamic acids: unveiling their role in stress resilience and human health - González-Rodríguez, Tzitziki; García-Lara, Silverio (Frontiers in Nutrition, 2024)
Maize production is pivotal in ensuring food security, particularly in developing countries. However, the crop encounters multiple challenges stemming from climatic changes that adversely affect its yield, including biotic and abiotic stresses during production and storage. A promising strategy for enhancing maize resilience to these challenges involves modulating its hydroxycinnamic acid amides (HCAAs) content. HCAAs are secondary metabolites present in plants that are essential in developmental processes, substantially contributing to defense mechanisms against environmental stressors, pests, and pathogens, and exhibiting beneficial effects on human health. This mini-review aims to provide a comprehensive overview of HCAAs in maize, including their biosynthesis, functions, distribution, and health potential applications.